Molecular mechanisms linking excess adipose tissue with esophageal cancer : targeting tumor metabolism and 5-lipoxygenase - Useckaite, Zivile (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Surgery, 2017)
Oesophageal adenocarcinoma (OAC) is the fastest growing cancer in the developed world. Visceral obesity, and in particular factors secreted from metabolically active visceral adipose tissue, may alter tumour glycolytic pathways resulting in a more aggressive phenotype. Despite major improvements to patient outcomes, less than 20% of OAC patients remain alive 5 years after diagnosis. The rising incidence of OAC is attributed to increases in the prevalence of obesity. The mechanisms linking obesity and OAC are not fully understood, however, it is thought that visceral obesity has more relevance to the pro-carciogenic alterations than subcutaneous obesity. Strong preliminary data using an Affymetrix array platform demonstrated glycolysis to be one out ofthree most upregulated pathways (alongside with EMT and cytokine signalling) following co-culture of oesophageal adenocarcinoma cells with adipose explants from OAC patients. Subsequent KEGG pathway analysis showed 5-lipoxygenase (5LOX) to be one ofthe top ten significantly upregulated genes in OAC. 5LOX is an enzyme involved in the metabolism of arachidonic acid to pro-inflammatory bioactive lipids. It has been linked to cancer with roles in inflammation, tumourigenesis and overall survival. The aim of this project was to delineate how excess visceral adiposity affects tumour metabolism and to investigate the role of commercially available and novel inhibitors of the glycolytic pathway and 5LOX as anti-cancer agents in obesity-driven oesophageal Cancer.
Keywords: Surgery, Ph.D.; PhD Trinity College Dublin, 2017